(NrAZNYE DNI WOJNY(B. (NdNEWNIK PISATELQ(B: [(NbIOGRAFIQ(B]; s 1941 (NGOD(B: (NtOM (B1 / s (N~ASTX (B8s - (NsIMONOW(B, (NkONSTANTINs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1982)
(NnASTOQ]IJ TOM SOSTAWILI WOENNYE DNEWNIKI k(B. (Nm(B. (NsIMONOWA(B, (NW TO WREMQ KORRESPONDENTA (B"(NkRASNOJ ZWEZDY(B", (NOHWATYWA@]IE SOBYTIQ (B1941 (NGODA(B.s
rus
Keywords: (NdNEWNIKIs; (NbIOGRAFIQs